Durability of Newly Developed Polyphenylene-Based Ionomer Membranes in Polymer Electrolyte Fuel Cells: Accelerated Stress Evaluation. Issue 7 (27th March 2019) - Shimizu, Ryo; Otsuji, Kanji; Masuda, Akihiro; Sato, Nobuyuki; Kusakabe, Masato; Iiyama, Akihiro; Miyatake, Kenji; Uchida, Makoto
Abstract : The chemical durability of the hydrocarbon (HC) polymer electrolyte membrane, sulfonated poly(phenylene) quinquephenylene (SPP-QP), is evaluated at 90°C and 160 kPaG pressure of hydrogen and air supplying anode and cathode, respectively, under open circuit voltage (OCV) conditions as an accelerated stress test in a polymer electrolyte fuel cell (PEFC). To evaluate the degree of deterioration of the membranes, exhaust water is collected from both electrodes periodically during the tests, and the chemical species are analyzed by ion chromatography (IC). The SPP-QP membrane-based cell with appropriate gaskets and gas diffusion layers (GDL) shows the highest durability, in comparison with several other cells, and exhibits a high OCV for more than 1000 h and the lowest emission rate of sulfate (30 μg cm −2, 2.6% loss) accumulated over 1000 h. We conclude that the simple hydrophilic structure and hydrophobic structure of the SPP-QP membrane, consisting solely of phenylene groups, leads to remarkably high intrinsic chemical stability and stability during the OCV stress evaluation; however, it also makes the membranes brittle. We also suggest that this negative aspect of the SPP-QP membrane might be mitigated by use of appropriate cell components such as gaskets and GDLs.